Quintic trigonometric Bezier curve and its maximum speed estimation on highway designs - Misro, M. Y.; Ramli, A.; Ali, J. M. (AIP conference proceedings, 2018)
This paper describes a new function called quintic trigonometric Bezier curve that has the potential to estimate the maximum driving speed allowed for safe driving on roads. The shape parameters present in this trigonometric Bezier function gives more flexibility for users in designing highways. Since the curves do interpolate the points, small changes in shape parameters will affect the curvature of the curve, therefore creating a bigger difference towards speed estimation. The objective of this articles is to conclude curvature information of quintic trigonometric Bezier curves with the goal of approximating roads’ maximum speed and estimating the maximum allowed speed.